Goods Pawning Practices in Bilalang Satu Village and Their Conformity with Islamic Economic Principles - Faradila Hasan; Evra Willya; Siti Sugianti Ngurawan; Moh. Muzwir R. Luntajo (Bulletin of Islamic Research, 2024)
Bilalang Satu Village is a village in Bilalang Subdistrict, Bolaang Mongondow Regency, North Sulawesi, where the majority of residents are Muslim. On several occasions, they have engaged in pawning practices to meet financial needs. Unfortunately, the current pawning practices are deemed non-compliant with Islamic Law, for example: 20% monthly interest rates without time limits, smaller loan amounts compared to the pawned item's value, creditor intimidation during default, and weak legal instruments protecting pawn customers. The community's lack of understanding regarding Sharia pawning further aggravates this situation. This study aims to analyze the Sharia compliance of pawning practices in Bilalang Satu Village and formulate recommendations for reform. The research utilizes a qualitative method with a case study approach. Data collection is conducted through in-depth interviews, observations, documentation review of pawning contracts, and literature review. The collected data is then qualitatively analyzed from an Islamic economic perspective. The results show that asset pawning in this village has minimal compliance with Sharia principles and provisions, making it potentially exploitative and detrimental to villagers. The recommendations formulated include: massive socialization and regulation of Sharia pawning, establishment of a Sharia Pawning Cooperative, as well as sustainable educational and assistance programs. These reform efforts require a participatory approach to be genuinely accepted by villagers. Thus, it is hoped that pawning practices in Bilalang Satu Village will be able to align with the principles of justice in the Islamic economy.